Vision‐based tip position tracking control of two‐link flexible manipulator. Issue 2 (1st June 2020) - Sahu, Umesh Kumar; Patra, Dipti; Subudhi, Bidyadhar
Abstract : Owing to the non‐collocation of actuators and sensors in a flexible‐link manipulator (FLM) it becomes difficult to achieve accurate tip position tracking. To resolve this issue, a vision sensor is used for direct measurement of the tip position instead of employing the traditional mechanical sensors. Among the different visual servoing (VS) control schemes, image‐based VS (IBVS) is more effective. However, there are many challenges in the IBVS scheme such as singularities in the interaction matrix and local minima in trajectories that affect the system performance in real‐time applications. In this study, the moment‐based new visual feature is selected to address the aforesaid issues that arise in the IBVS scheme. Furthermore, a new two‐time scale IBVS controller is developed for addressing the tip‐tracking control problem of the two‐link flexible manipulator (TLFM). In the proposed control scheme, the dynamics of the FLM is decomposed into two‐time scale models, namely a slow subsystem and a fast subsystem. The performance and robustness of the proposed new two‐time scale IBVS controller for TLFM are verified by pursuing simulation studies. It is observed from the obtained results that the proposed controller effectively stabilises the oscillatory dynamics and tracks the reference trajectory accurately.